(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new classes of multifunctions between bitopological spaces, namely upper contra-(τ_1,τ_2)-continuous multifunctions and lower contra-(τ_1,τ_2)-continuous multifunctions. Moreover, several characterizations and some properties concerning upper contra-(τ_1,τ_2)-continuous multifunctions and lower contra-(τ_1,τ_2)-continuous multifunctions are investigated.